An unusual case of massive hemoptysis due to Bacillus cereus necrotizing pneumonia. (2019) - Leung, Eric C.; McFadden, Sean; Tremblay, Alain
Abstract: Bacillus cereus is a gram-positive bacillus that is ubiquitously present in the environment, often regarded as a contaminant when isolated in clinical testing. Cases of B. cereus causing lower respiratory tract infections are sparse, with less than 20 reported in the literature, and even fewer as a cause of massive hemoptysis. The majority of cases occur in the setting of an immunosuppressed patient. We describe a case of a 59-year-old male with esophageal adenocarcinoma undergoing chemotherapy presenting with a right upper lobe necrotizing pneumonia secondary to B. cereus with consequent massive hemoptysis.